SEISMIC VELOCITY DETERMINATION IN GRAVEL AND SANDS USING PIEZOCRYSTALS - Santamarina Juan Carlos; Imhof Luis Armando (Earth Sciences Research Journal)
The exact determination of seismic waves' propagation velocities has great importance in the geotechnics due to from that it is possible to determine, among other parameters, the dynamic ones: Elasticity E, Rigidity G, Poisson !, compressibility B; as well as to reach a knowledge on the stress-strain behavior for the studied soil samples. The seismic waves transmission considered in tests at laboratory scale carried out in the present work is a phenomenon that produces very small deformation, and so doesn't disturb the material. This allows to apply the results in a more general scale to study the behavior of soils in situ and to predict their answer to stress. With the purpose to study the response of particulate material subjected to seismic excitements at small scale, samples of gravels and sands were successively introduced in an odometric cell, exciting them with impulsive signals and registering the corresponding seismograms through general purpose piezoelectric transducers embedded in ends of the cell. The distance source-receiver was interval increased, which enabled, from the corresponding regression straight lines, to calculate in precise form the propagation velocities (for P waves). The tests were carried out in samples of dry alluvial soil with three different grain sizes. The respective frequency spectra of the signals were determined for two packing modes: loose and compact, what added information on the medium characteristics.